ALDENOURA DE SA PORTO: THE HISTORY OF AN EXCLUSION - Walker, Marli; Souza Pinto, Luiz Renato de [UNESP] (Univ Estado Mato Grosso, 2019)
This text presents the initial phase of the research regarding the exclusion of Aldenoura de Sa Porto from the History of Literature of Mato Grosso - century XX, by Hilda Gomes Dutra Magalhaes. The study of the written rescue and revisionism occurred due to the access to the research report, in which, the work of the female prose writer is inserted. Curiously, the excerpts and analyzes are not included in the book published in 2001, by the professor and researcher of the Federal University of Mato Grosso. Based on this rescue, it is attempted, to hypothesize in order to understand the removal of the female prose writer from the historiographic compendium and also problematize the exclusionary of significant and voluminous written work by woman.
Keywords: Aldenoura de Sa Porto; History of Literature of Mato Grosso; woman; literature